Development and evaluation of orally disintegrating tablets containing the mosapride resin complex - Wu Tong; Wang Guanhua; Shi Caihong; Li Jinghan; Zhao Na; Dong Zihao; Pan Weisan; Zhang Xiangrong (Acta Pharmaceutica)
The purpose of this study was to prepare a mosapride citrate-resin (Amberlite® IRP 88) complex and orally fast-disintegrating tablets of the resin complex. The resinate complex of mosapride-Amberlite® IRP 88, mass ratio 2:1, was prepared in an ethanol-water solution. The effects of alcohol concentration, temperature, and pH of the solution on complex formation were evaluated. The complex physicochemical properties were characterized by differential scanning calorimetry, X-ray diffraction and scanning electron microscopy. Orally disintegrating tablets were prepared by direct compression and were optimized using the response surface method. Optimized orally fast-disintegrating tablets disintegrated within 18 s. The pH dependence of mosapride release from the tablet decreased drug dissolution in simulated saliva, whereas it promptly released in the pH 1.0 solution. The data reported herein clearly demonstrate that tablets containing the mosapride-Amberlite® IRP 88 complex for oral disintegration could be particularly useful for patients with swallowing difficulties.